Jebel al-Mutawwaq - Polcaro, Andrea; Muñiz, Juan Ramon; Caselli, Alessandra (Brepols, 2024)
The Early Bronze Age site of Jebel al-Mutawwaq, located on a hill overlooking the Zarqa River in Jordan, was a thriving centre of population from the second half of the fourth millennium into the third millennium <span class=